Leveraging Social Networks for the Assessment and Management of Neurological Patients - Dhand, Amar; Podury, Archana; Choudhry, Niteesh; Narayanan, Shrikanth; Shin, Min; Mehl, Matthias R. (Seminars in Neurology, 2022)
Social networks are the persons surrounding a patient who provide support, circulate information, and influence health behaviors. For patients seen by neurologists, social networks are one of the most proximate social determinants of health that are actually accessible to clinicians, compared with wider social forces such as structural inequalities. We can measure social networks and related phenomena of social connection using a growing set of scalable and quantitative tools increasing familiarity with social network effects and mechanisms. This scientific approach is built on decades of neurobiological and psychological research highlighting the impact of the social environment on physical and mental well-being, nervous system structure, and neuro-recovery. Here, we review the biology and psychology of social networks, assessment methods including novel social sensors, and the design of network interventions and social therapeutics.
Keywords: social connection; social networks; psychosocial interventions; neurobiology; neuropsychiatry; mobile sensing